PEMBUATAN PUPUK ORGANIK CAIR DARI SAMPAH RUMAH TANGGA YANG DIAPLIKASIKAN PADA TANAMAN OBAT KELUARGA DI KELURAHAN MUARA JAWA TENGAH, KUTAI KARTANEGARA - Imam Rohadi; M. Rizky Wardani; Nila Puspita Sari; Resya Winda Alya Khalisa; Gilang Yuda Pratama (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2025)
Waste management remains a critical issue in Muara Jawa Tengah Village. Household activities generate both organic and inorganic waste. However, the organic waste produced in the area is still underutilized and often contributes to environmental pollution. This activity aimed to convert household organic waste into liquid organic fertilizer (LOF), which can be applied to family medicinal plants (TOGA), thereby enhancing its utility and environmental value. The method implemented involved the production of LOF through the fermentation of household organic waste using effective microorganisms (EM4). The resulting LOF was a yellowish-brown liquid with a characteristic fermentation aroma. The presence of this aroma indicates successful anaerobic fermentation, wherein organic compounds such as carbohydrates, proteins, and lipids were decomposed into simpler compounds. These compounds are rich in essential macronutrients (N, P, and K) as well as various beneficial micronutrients. These nutrients play a significant role in supporting plant growth and development. Based on the findings, it can be concluded that LOF was successfully produced from household organic waste with the aid of EM4 and was effectively applied to TOGA in the Muara Jawa Tengah Village. Keywords: Family Medicinal Plants, Liquid Organic Fertilizer, Organic Waste